PLASMA ION EMISSION FROM HIGH-INTENSITY PICOSECOND LASER-PULSE INTERACTIONS WITH SOLID TARGETS - Fews, A; Norreys, P; Beg, F; Bell, A; Dangor, A; Danson, C; Lee, P; Rose, S (1994)
The fast ion emission from high intensity, picosecond laser plasmas has been measured to give the characteristic ion energy and the amount of laser energy transferred to ions with energies 100 keV/nucleon as a function of incident intensity. The characteristic ion energy varies from 0.2 to 1.3 MeV over the range 2.0 × 1017-2.0 × 1018 W cm-2. 10% of the laser energy is transferred into MeV ions at 2.0 × 1018 W cm-2. Calculations of stopping power in high density materials are presented that show that fast ions cannot be ignored in modeling fast ignitor schemes. © 1994 The American Physical Society.